2018
DOI: 10.3847/2041-8213/aaadbd
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Evolution of Titan's Stratosphere Near the Poles

Abstract: In this Letter, we report the monitoring of seasonal evolution near Titan's poles. We find Titan's south pole to exhibit since 2010 a strong temperature decrease and a dramatic enhancement of several trace species such as complex hydrocarbons and nitriles (HC 3 N and C 6 H 6 in particular) previously only observed at high northern latitudes. This results from the seasonal change on Titan going from winter (2002) to summer (2017) in the north and, at the same time, the onset of winter in the south pole. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 22 publications
6
40
0
Order By: Relevance
“…Vinatier et al (2015), using limb viewing observations, showed the vertical gradient of C 3 H 4 increases dramatically over the mid northern latitudes as northern winter moves into northern spring and the polar vortex responds to the changing amount of sunlight. Coustenis et al (2018), using nadir observations to probe abundance in a narrow altitude range in the middle stratosphere, show a similar trend at latitudes closer to the pole, between 60 • and 90 • either side of the equator. In the same studies, propane was shown to have a more constant abundance in latitude and time, remaining constant within error bars near 1×10 −6 throughout the stratosphere, with the exception near the winter pole, where it increases with altitude.…”
Section: Introductionmentioning
confidence: 67%
“…Vinatier et al (2015), using limb viewing observations, showed the vertical gradient of C 3 H 4 increases dramatically over the mid northern latitudes as northern winter moves into northern spring and the polar vortex responds to the changing amount of sunlight. Coustenis et al (2018), using nadir observations to probe abundance in a narrow altitude range in the middle stratosphere, show a similar trend at latitudes closer to the pole, between 60 • and 90 • either side of the equator. In the same studies, propane was shown to have a more constant abundance in latitude and time, remaining constant within error bars near 1×10 −6 throughout the stratosphere, with the exception near the winter pole, where it increases with altitude.…”
Section: Introductionmentioning
confidence: 67%
“…Titan's emitted power in the wavenumber ranges of FP3 and FP4 decreased from 2004 to 2017 in the tropical region and the SH, but the temporal variations in the middle and high latitudes of the NH are complicated. The complicated behaviors of Titan's emitted power in the middle and high latitudes of the NH are probably related to other activities in the high atmosphere (e.g., Coustenis, 2005;Coustenis et al, 2018;Teanby et al, 2008Teanby et al, , 2012West et al, 2018). Therefore, the decreasing emitted power from 2004 to 2017 recorded by FP3 and FP4 in the tropical region and the SH is related to the decreasing solar flux in the same regions (panel B of Figure 1).…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, the decreasing emitted power from 2004 to 2017 recorded by FP3 and FP4 in the tropical region and the SH is related to the decreasing solar flux in the same regions (panel B of Figure 1). The complicated behaviors of Titan's emitted power in the middle and high latitudes of the NH are probably related to other activities in the high atmosphere (e.g., Coustenis, 2005;Coustenis et al, 2018;Teanby et al, 2008Teanby et al, , 2012West et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…These FP3 and FP4 data were used for many purposes: to map latitude variations of trace gases (e.g. Coustenis et al 2007Coustenis et al , 2010Teanby et al 2010a;Bampasidis et al 2012;Coustenis et al 2013Coustenis et al , 2016Coustenis et al , 2018, see also MIDIRTMAP), to measure isotopic ratios of hydrocarbons (Nixon et al 2008b) and to search for new species (Jolly et al 2015).…”
Section: Firnadcmpmentioning
confidence: 99%